1994
DOI: 10.1002/stem.5530120603
|View full text |Cite
|
Sign up to set email alerts
|

Hemopoietic stem cells: Analysis of some parameters critical for engraftment

Abstract: In this review four parameters relevant to the grafting of hemopoietic stem cells (HSC) are analyzed: the nature and amounts of grafted HSC, the sources of HSC and the "in vivo" fate of the grafted cells. One may oppose cells with short-term repopulating ability to cells with long-term reconstitutive capacity. The former comprise progenitors, while the latter consist of primitive stem cells, corresponding to murine pre-colony forming units-spleen (pre-CFU-S) (and to some murine CFU-S) or to human pre-colony fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 125 publications
1
10
0
Order By: Relevance
“…This hypothesis supports the finding that the administration of large numbers of reconstituting cells that represent heterogeneous populations appears to be a cautionary procedure, since it should ensure polyclonal hemopoiesis after bone marrow transplantation (BMT) [10]. The cyclic processes of cell proliferation and differentiation are both stochastic on one or few cell levels and controlled on compartment and organ levels [11].…”
Section: Introductionsupporting
confidence: 75%
“…This hypothesis supports the finding that the administration of large numbers of reconstituting cells that represent heterogeneous populations appears to be a cautionary procedure, since it should ensure polyclonal hemopoiesis after bone marrow transplantation (BMT) [10]. The cyclic processes of cell proliferation and differentiation are both stochastic on one or few cell levels and controlled on compartment and organ levels [11].…”
Section: Introductionsupporting
confidence: 75%
“…Mature stem cells would be expected to exhibit a lower potency than primitive stem cells and therefore a lower engraftment potential. From a practical viewpoint this means that mature stem cells would be expected to demonstrate short-term engraftment [22][23][24][25] and reconstitution while more primitive stem cell would demonstrate long-term engraftment and reconstitution [22,25,26]. As a result, measuring the potency of just a single stem cell population, especially a mature stem cell population, could result in a false interpretation and conclusion.…”
Section: Measuring the Potency Ratiomentioning
confidence: 99%
“…In vivo labeling kinetics during 2 [H]-glucose infusion were determined for CD41a (megakaryocyte lineage) and for glycophorin A (erythroid lineage)-expressing cells remaining in marrow samples after CD34 ϩ cell selection. Glycophorin A ϩ cells had a mean t 1/2labeling of 3.5 days (range, 2-6 days) ( Table 5).…”
Section: In Vivo Turnover Kinetics Of Erythroid and Megakaryocyte Linmentioning
confidence: 99%
“…Subpopulations of hematopoietic progenitors not only differ in their selfrenewal, proliferation, and differentiation capacities, [1][2][3][4][5] but they also have different cell cycle and turnover kinetics. [1][2][3][6][7][8] For example, in vivo bromodeoxyuridine (BrdU)-labeling studies demonstrated that murine marrow primitive progenitors capable of long-term reconstitution of lethally irradiated mice have turnover times of 30 days or longer. 6,7 In contrast, granulocyte/macrophage committed progenitors have rapid turnover times of only 1 to 2 days.…”
Section: Introductionmentioning
confidence: 99%